PENGARUH KEDISIPLINAN KERJA DAN KINERJA KARYAWAN TERHADAP PENERAPAN TOTAL QUALITY MANAJEMEN DI OEMAH DJOWO CLASSIC OTO RESTO YOGYAKARTA - Qurrata Ayunina C.H. (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2019)
Quality is a major factor in order to survive in the business’s competition. So the quality being the main things that should be done by each company. In order to increase the quality of human resources, corporate can implement total quality management (TQM), by which an employee should do a job better, more effective and more efficient in producing the products with high quality. This research was aimed to know the influence of working discipline, working performance and the implementation of total quality management (TQM) at Oemah Djowo Classic Oto Resto Yogyakarta.This research method used is the quantitative approach. The populations in this research were 40 people and all were respondents. The result showed that working discipline and working performance has a significant influence for the implementation of Total Quality Management (TQM) at Oemah Djowo Classic Oto Resto Yogyakarta.